Consumer Global Orientation and Its Impact on Consumers’ Positive Emotions - Sulhaini; Dayani, Rahman; Sulaimiah; Rusdan (Universitas Prasetiya Mulya, 2018)
The objective of this study is to examine the role of consumer global orientation and the inferior image of foreign brands in young, educated consumers’ admiration for foreign brands and their willingness to pay more for foreign brands. The sample of this study was used students of the University of Mataram. Data collected in a classroom at the end of lecture by using a carefully developed instrument that has been carefully developed and well validated. Its findings suggest that consumer global orientation and the inferior image of local brands have no direct effect on consumers’ willingness to pay more for foreign brands. Nonetheless, they do indirectly affects consumer intentions by creating positive emotions about foreign brands. This positive emotion, i.e. foreign brand admiration, seems to have a critical role, as it fully mediates the effects of the two constructs. Consumer global orientation and the inferior image of local brands nurture consumers’ positive views of foreign brands, which in turn increase consumer willingness to pay higher prices for foreign brands. This study also conceptualizes consumer global orientation and provides the essential recommendations for future research.